Nicotinamide mononucleotide adenylyltransferase displays alternate binding modes for nicotinamide nucleotides. (1st October 2015) - Pfoh, Roland; Pai, Emil F.; Saridakis, Vivian
<x xml:space="preserve">Abstract</x> Nicotinamide mononucleotide adenylyltransferase (NMNAT) catalyzes the biosynthesis of NAD+ and NaAD+. The crystal structure of NMNAT from Methanobacterium thermoautotrophicum complexed with NAD+ and SO42− revealed the active‐site residues involved in binding and catalysis. Site‐directed mutagenesis was used to further characterize the roles played by several of these residues. Arg11 and Arg136 were implicated in binding the phosphate groups of the ATP substrate. Both of these residues were mutated to lysine individually. Arg47 does not interact with either NMN or ATP substrates directly, but was deemed to play a role in binding as it is proximal to Arg11 and Arg136. Arg47 was mutated to lysine and glutamic acid. Surprisingly, when expressed in Escherichia coli all of these NMNAT mutants trapped a molecule of NADP+ in their active sites. This NADP+ was bound in a conformation that was quite different from that displayed by NAD+ in the native enzyme complex. When NADP+ was co‐crystallized with wild‐type NMNAT, the same structural arrangement was observed. These studies revealed a different conformation of NADP+ in the active site of NMNAT, indicating plasticity of the active site.